Technoeconomic Analysis of Photovoltaics Module Manufacturing with Thin Silicon Wafers - Liu, Zhe; Sofia, Sarah E.; Laine, Hannu; Woodhouse, Michael; Wieghold, Sarah; Peters, Ian Marius; Buonassisi, Tonio (Conference Record of the IEEE Photovoltaic Specialists Conference, 2019)
Reducing silicon usage by adopting thinner wafers can significantly reduce capital expenditure (capex) and cost, and thus accelerate the growth of manufacturing capacity and deployment. In this work, we evaluated potential benefits of thin Si wafers for current and future PV modules. We apply a technoeconomic framework that couples bottom-up cost model, and a cash-flow growth model to analyze PV modules with thin wafers. First, we show that, comparing the current PERC with 160 μm thick wafers to the high-efficiency concept with 50 μm thin wafers, the capex is reduced from 0.39 to 0.2 /(W/year) while the cost is from 0.32 to 0.2 W. Second, the potential of accelerated deployment is analyzed for the high-efficiency thin wafer concept. We found the significant advantages of higher growth rate (∼20% relative) and higher deployment plateau (∼3 times) than the current PERC modules.
CRIS-Team Scopus Importer:2022-06-05
Keywords: PV manufacturing; technoeconomic analysis; thin silicon wafers